Idiopathic Omental Infarction, Diagnosed and Managed Laparoscopically: A Case Report. (26th August 2013) - AbdulAziz, Ahmed; El Zalabany, Tamer; Al Sayed, Abdul Rahim; Al Ansari, Ahmed
Abstract : Idiopathic omental infarction is a rare cause of acute abdomen in adults, and the clinical finding can mimic acute appendicitis. Although idiopathic omental infarction is uncommon, the incidence of its detection has become more frequent as a result of advances in radiological technologies. We reported on a 21-year-old man who presented with sudden onset of intermittent right lower quadrant abdominal pain for seven days. The pain became more localized at the right iliac fossa (RIF) at day 2 before admission. A physical examination revealed a fever (38.2 ∘ C ), severe RIF tenderness, mass-like fullness, and positive rebound tenderness. A CT of the abdomen showed inflammatory changes and increased fat density mass in the right upper quadrant measuring 5 × 4  cm representing focal panniculitis. However, the appendix was visualized normally and the findings were not in favor of acute appendicitis. Diagnosis was carried on laparoscopically. Serosanguinous free fluid was found in all abdominal quadrants. A 6 × 4  cm gangrenous omental mass was noted. The omental mass was excised and an appendectomy was performed. In summary, omental infarction should be considered as a deferential diagnosis for acute right-sided abdominal pain, especially if the clinical finding does not correspond to appendicitis.